A British Madame Bovary. On „The Doctor’s Wife” by Mary E. Braddon - Aleksandra Budrewicz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
This article is a comparative analysis of Mary Elizabeth Braddon’s The Doctor’s Wife and Gustave Flaubert’s Madame Bovary. Braddon’s novel has been interpreted as an imitation of Flaubert’s. The basis of the analysis is a Polish translation of Braddon’s novel (Żona doktora, „Gazeta Warszawska” 1867). This translation was published earlier than the translation of Madame Bovary (1878). Braddon’s works were quite popular in Poland and they were translated into Polish as well. It is shown that Braddon’s novel was not a copy of Flaubert’s work. The similarities concern the plot (a married woman’s affair) and psychological characterisation of the eponymous character (a girl who is absorbed her books and lives in the world of fantasy). In the crucial scene of the novel, Braddon makes a different choice than Flaubert does: her protagonist, who is in love with a seducer, does not commit adultery. Braddon explained that this was due to Protestantism and platonic concept of love which does not need physical involvement. Braddon shows three stages of the protagonist’s history: 1) her youth filled with books; 2) her unhappy marriage (the wife does not love the husband but the seducer); 3) after her husband’s and lover’s deaths the protagonist receives a large amount of money and begins to perform important social roles. This is how Braddon criticises the educational system of Victorian England and depicts a model which is a form of pedagogy preparing people for practical life.